Beta-blockers: once or three times a day?. Issue 6124 (27th May 1978) - Reybrouck, T; Amery, A; Fagard, R; Jousten, P; Lijnen, P; Meulepas, E
Abstract : In a double-blind, crossover trial 16 hypertensive patients were treated, in random order, with placebo, metoprolol 300 mg in a single daily dose, or metoprolol 300 mg/day in three doses. Both therapeutic regimens produced detectable plasma metoprolol concentrations and appreciable beta-blockade, estimated from exercise tachycardia, throughout the day. Fluctuations throughout the day in plasma drug concentrations and degree of beta-blockade were insignificant on the thrice-daily regimen, but they varied considerably on the single-dose regimen. Both therapeutic regimens also significantly lowered blood pressure throughout the day. Although the thrice-daily regimen again tended to produce a stronger and less fluctuating hypotensive action, the differences in hypotensive effect between the two regimens were not statistically significant. A single-dose of 300 mg of metoprolol can therefore be recommended if the only aim is to reduce blood pressure but not if a steady degree of beta-blockade is needed.